محمد حمید شاہد کے افسانوی مجموعہ”سانس لینے میں درد ہوتا ہے“ کا سانحاتی تناظر میں تجزیہ: A Tragic Analysis of Muhammad Hameed Shahid’s Short Story Collection “Saans Lene Mein Dard Hota Hai” (Research Journal Tahqeeqat, 2025)
The presented text offers a comprehensive critical analysis of Muhammad Hameed Shahid’s short stories from his acclaimed collection "Saas Lene Mein Dard Hota Hai", published in 2019. Central to the discussion is the story "Quetta Mein Kuchlak", which reflects the post-9/11 socio-political landscape of Pakistan, particularly the deteriorating security and ethnic tensions in Balochistan. Through an introspective and unnamed narrator, Shahid masterfully captures the pervasive fear, identity crisis, and human vulnerability in a region transformed by terrorism, state surveillance, and linguistic division. The metaphor of "Guwanko" symbolizes the internalization of fear and the alienation from one’s own identity. In addition, the analysis extends to other stories in the collection—"Baqi Umar Izafi Hai", "Khooni Lamha Waqt-e-Laam Bachon Ka", "Aik Musalsal Zargasht", "Saas Lene Mein Dard Hota Hai", and "Jang Mein Mohabbat Ki Tasveer Nahin Banti"—each unraveling various dimensions of individual and collective trauma. These narratives explore themes such as psychological disintegration, maternal agony, corruption, war-induced displacement, and the tragic loss of children in terrorist attacks. Whether addressing existential despair, institutional failure, or the collapse of human connection, Shahid’s stories weave a layered and symbolic tapestry of postmodern Pakistani life. Overall, this critique reveals how Muhammad Hameed Shahid uses fiction as a means to document national tragedies and intimate suffering, crafting stories that stand at the intersection of memory, politics, identity, and humanity. His fiction resonates as both a personal lament and a socio-political commentary, offering a profound meditation on what it means to live, suffer, and survive in a fractured, fear-ridden world.